Analisis Indirect Harga Tembakau Terhadap Pola Konsumsi Keluarga Pada Petani Di Desa Sukorejo - Safitri, Indah Nurlaili; Sulistiana, Erinda; Pradani, Rizki Febri Eka (CV. Kalimasada Group, 2023)
Indirect tobacco prices influence the consumption patterns of tobacco farming families in Sukorejo Village. The aim of this research is to better understand the indirect impact of tobacco prices on people's purchasing decisions and how this influences the consumption patterns of tobacco farming families. This research uses a qualitative approach with researchers conducting direct interviews and documentation as instruments. The population studied were tobacco farmers in Sukorejo Village, Kotaanyar District. The results of the interviews show that: (1) Indirect tobacco prices influence the consumption patterns of tobacco farming families in Sukorejo Village. (2) Tobacco farming is able to meet the economic needs of farming families. (3) the income from tobacco farming in Sukorejo Village is very good. The conclusion is that indirect tobacco prices influence the consumption patterns of tobacco farming families in Sukorejo Village and also the income from tobacco farming can meet the needs of their families during one harvest, but farmers also seek additional income through other jobs such as construction workers, animal husbandry, and home businesses such as selling meatballs, cilok , and so forth.